2020
DOI: 10.2147/ott.s232839
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long Non-Coding RNA LEF1-AS1 Promotes Migration, Invasion and Metastasis of Colon Cancer Cells Through miR-30-5p/SOX9 Axis</p>

Abstract: Introduction: Aberrant expression of long non-coding RNAs (lncRNAs) has been implicated in the tumorigenesis and progression of colon cancer. Lymphoid enhancer-binding factor 1 antisense RNA 1 (LEF1-AS1), a highly conserved and newly discovered long noncoding RNA, has been reported to be upregulated and correlated with poor prognosis in colon cancer, but the exact role of it remains uncertain. Materials and Methods: In our study, the biological functions of LEF1-AS1 in colon cancer were analyzed by cell viabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…To further explore the underlying functions of lncRNAs in ACS, co-expression of lncRNAs with their associated coding genes was performed based on the degree of correlation. Among the top 10 elevated and decreased lncRNAs according to the degree, NR_029374 with 12 degrees was upregulated, consistent with the results obtained by Sun et.al [34] , who reported that NR_029374 was upregulated in CC and correlated with poor overall survival. NR_029374 promoted the migration, invasion, and metastasis of CC through the miR-30-5p/SOX9 axis and this nding was supported by previous results [35] .…”
Section: Discussionsupporting
confidence: 91%
“…To further explore the underlying functions of lncRNAs in ACS, co-expression of lncRNAs with their associated coding genes was performed based on the degree of correlation. Among the top 10 elevated and decreased lncRNAs according to the degree, NR_029374 with 12 degrees was upregulated, consistent with the results obtained by Sun et.al [34] , who reported that NR_029374 was upregulated in CC and correlated with poor overall survival. NR_029374 promoted the migration, invasion, and metastasis of CC through the miR-30-5p/SOX9 axis and this nding was supported by previous results [35] .…”
Section: Discussionsupporting
confidence: 91%
“…Biotinylated Bio‐NC, Bio‐miR‐362‐5p‐wt, and Bio‐miR‐362‐5p‐mut were selected and the assay was performed as previously described 19 . GAS5 expression was detected by RT‐qPCR.…”
Section: Methodsmentioning
confidence: 99%
“…LncRNA-lymphoid enhancer-binding factor 1 antisense RNA 1 (lncRNA-LEF1-AS1) is highly expressed in colorectal cancer and positively correlated with the dismal prognosis of patients [ 247 ]. In this study, it was further observed that lncRNA-LEF1-AS1 heightens the capability of colorectal cells to grow under anchorage-independent conditions and metastasize to lungs through repressing the activity of miR-30-5p to target the sex-determining region Y box 9 (SOX9) [ 247 ], which is a pro-survival, -stemness, and -metastasis factor [ 261 , 262 , 263 ]. In line with this, SOX9 was described to support anoikis resistance by promoting the stemness property of cancer cells [ 264 ] ( Figure 3 and Table 3 ).…”
Section: Long Noncoding Rnas Anoikis and Anchorage-independent Gmentioning
confidence: 99%